A Robust Steganography method Using Adjustable Parameters - Ahmad Reza Eskandari (Institute of Advanced Engineering and Science, 2013)
In this paper, a new steganography method based on contourlet transform is presented. Compared with the previous works, the proposed method causes far fewer distortions in high frequency coefficients. This significantly increases the quality of stegano image and extracted secret image and its robustness against to steganalysis algorithm. Furthermore, we proposed two adjustable parameters that could be suited in direction of changing the quality of stegano image and extracted secret images or its robustness against to attacks and steganalysis algorithms. Using these parameters, much better performance of storing data is accessible. The proposed algorithm has higher robustness against to steganalysis algorithm in comparison with related state of the art methods. Likewise, the experimental results show robustness respect to Gaussian noise and other attacks such as JPEG compression.DOI:http://dx.doi.org/10.11591/ijece.v3i2.2236